Knowledge Of School Health Programmes Among Teachers In Schools, Gulmi - Shrestha, Rhinu (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: School teachers should have basic knowledge regarding school health programs to provide promotive and preventive healthcare through the implementation of the program. Thus, the main objective of the study was to assess the knowledge of school health programs among school teachers in the schools of Gulmi. Method: A cross-sectional descriptive study was designed using a probability proportionate sampling technique and data from 73 respondents were collected using a self-developed structured questionnaire. The study was conducted between 2079/10/01 to 2079/10/30. Data management analysis and interpretation were done using descriptive and inferential statistics and presented in tabulated form. Result: In total, 49.3 % of the respondents had an adequate level of knowledge. Most (86.3 %) of respondents had a clear concept of the meaning. 90.4% of respondents had adequate knowledge of school health education. 58.9 % and 54.8% of respondents had adequate knowledge of Nutrition and health services, and school health nurses respectively. Only 46.9% of respondents had adequate knowledge of School health education. The study showed an association between the level of knowledge and the level of teaching area of the teachers (P=0.039). Conclusion: There was Less than half of the teachers had adequate knowledge on school health program. However, there are still gaps in knowledge on school health environment, Nutrition, and health services. Thus the training program should be provided by authorized level regarding this kind of components to enhance knowledge among teachers.